Introduction - Papadima-Sophocleous, Salomi; Kakoulli-Constantinou, Elis; Giannikas, Christina N. (My University, 2021)
University language centres provide language-based courses to students of all disciplines. The principal raison d’être of a university language centre is to support any number of learner types, with a variety of reasons for learning a second or foreign language at tertiary level. These may include students and staff, external partners, and members of the public as part of a wider outreach strategy (Critchley, 2015). Language centres offer credit-bearing language courses and language enhancement programmes, general education, and service learning subjects. They also offer subjects for postgraduate research students and masters programmes. Qualities of pedagogic innovation, institutional adaptability, and effective use of technology have contributed to language centres’ successful development (Ruane, 2003).
Keywords: Language centre; Research activities; Τertiary education language learning; Computer-assisted language learning; Language for specific purposes; Language teacher education; Research